Basic questions on end of life decisions : how do we know what's right? - Stewart, Gary (Gary P.); Cutre, William R.; Demy, Timothy J.; O'Mathuna, Donal P.; Cunningham, Paige C.; Kilner John F.; Bevingtonm Linda K. (Grand Rapids, MI : Kregel Publications, 1998)
Advances in medical technology have created ethical dilemmas for Christians in regard to death and dying. In this booklet, Christian scholars address such questions as suffering, removal of life support, organ donation, and self-determination.
Includes bibliographical references (p. 83).
Keywords: Death -- Religious aspects -- Christianity -- Miscellanea